Impact of the COVID-19 pandemic on psychological well-being of students in an Italian university: a web-based cross-sectional survey. (20th October 2021) - Villani, L; Pastorino, R; Molinari, E; Anelli, F; Ricciardi, W; Graffigna, G; Boccia, S
Abstract: Background: Italy was the first European country to implement a national lockdown because of the COVID-19 pandemic. Worldwide, this pandemic had a huge impact on the mental health of people in many countries causing similar reaction in terms of emotions and concerns at the population level. Our study investigated the impact of the COVID-19 pandemic on psychological well-being in a cohort of Italian university students. Methods: We conducted a cross-sectional survey in the period immediately after the first lockdown through the administration of a questionnaire on the personal websites of students attending their undergraduate courses at the Università Cattolica del Sacro Cuore. We used the Patient-Health-Engagement-Scale, Self-Rating-Anxiety-Scale, and Self-Rating-Depression-Scale to assess engagement, anxiety symptoms, and depression symptoms of our sample. Results: The sample size was 501 subjects, of which 35.33% were classified as anxious and 72.93% as depressed. Over 90% of respondents had good understanding of the preventive measures despite over 70% suffered from the impossibility of physically seeing friends and partners. Around 55% of students would have been willing to contribute much more to face the pandemic. An increase in the occurrences of anxiety was associated with being female, being student of the Rome campus, suffering from the impossibility of attending university, being distant from colleagues, and being unable of physically seeing one's partner. Performing physical activity reduced this likelihood. Conclusions: University students are at risk of psychological distress in the case of traumatic events. The evolution of the pandemic is uncertain and may have long-term effects on mental health. Therefore, it is crucial to study the most effective interventions to identify vulnerable subgroups and to plan for acute and long-term psychological services to control and reduce the burden of psychological problems.